The Influence of the Problem-Solving Learning Model on Student Learning Outcomes in Ecosystem Material at State Senior High School 9 Pekanbaru - Diah, Diah Orina; Ramadansur, Rahmat; Sembiring, Al Kludri; Dinata, Marta (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
Problem Solving is a learning model that presents material to students, is given problems to solve and gains knowledge in the process of finding, analyzing and solving a problem in a systematic and creative way to achieve the desired goal or solution, known as problem solving. This research aims to determine the influence of the problem solving learning model on learning outcomes in ecosystem material for students at SMA Negeri 9 Pekanbaru. The population in this study were all class X students of SMA Negeri 9 Pekanbaru for the 2024/2025 academic year. This research uses a quantitative method with a non-equivalent pretest-posttest control group design by managing data for a control class with a total of 45 students and an experimental class with a total of 45 students taken using a purposive sampling technique. The instruments in this research are teaching modules and problem solving LKPD. Data collection techniques include learning results tests and teacher and student activity sheets. Student learning results show that the average N-gain value for the control class is 0.31 (medium) while the average N-gain value for the experimental class is 0.58 (medium). The results of the N-Gain t-test obtained a sig value. (2-tailed) 0.00<0.05 then reject H0, meaning there is a significant difference in learning outcomes between the control class and the experimental class. So the conclusion of this research is that there is an influence of the problem solving learning model on learning outcomes in ecosystem material for students at SMA Negeri 9 Pekanbaru. Keywords: Problem Solving, Learning Models, Learning Outcomes, Ecosystem.